A SCIENCE NIGHT PROGRAM. - Collier, Jr., Robert (Education, 1936)
The article presents information on the bi-annual "Science Nights" program. The possibilities of the program are limited only by the imagination of the teachers and students concerned, and their willingness to put forth real effort in arranging the necessary displays. Every department in school has its share in such an event. Through an exhibit on consumer education, boys and girls are taught to read the labels found on a package. The program offers opportunities for the demonstration of talent of students in their various hobbies conducted outside school hours. Such activities as soap carving, the making of miniature airplanes, collecting stamps, poetry, flowers, and photography are given the space they require. The greatest value of such a program comes to the student who participates. He must know his project if he is to be questioned concerning it by the visitors to the demonstration.